2017
DOI: 10.21303/2504-5695.2017.00420
|View full text |Cite
|
Sign up to set email alerts
|

Substantiation of Hot Smoking Parameters Based on Sensory Researches in Hot Fish Marinades Technology in the Jelly Pouring

Abstract: Modern technologies of food products provide creation of healthy, tasty and safe products, characterized by high organoleptic properties, balance by main food factors and structural-mechanical parameters of a product. The main technological process in the technology of fish marinades and a jelly pouring is the hot smoking. Technological parameters of the hot smoking have been scientifically grounded on the base of the statistical processing of data of sensory studies. Organoleptic assessment of semi-products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…It has been found that ensuring stable structural and mechanical properties of dredge during refrigerated storage provides a ratio of 1 particle of low methoxylated pectin and 1 particle of alginic acid with a mass fraction of both structurants of at least 1.5 %. The resulting fill has a jelly strength of 112 g [7] and certain ratios ensure the absence of synergistic changes. Such strength of jelly corresponds to the high merchandising properties of the finished product.…”
Section: Research Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that ensuring stable structural and mechanical properties of dredge during refrigerated storage provides a ratio of 1 particle of low methoxylated pectin and 1 particle of alginic acid with a mass fraction of both structurants of at least 1.5 %. The resulting fill has a jelly strength of 112 g [7] and certain ratios ensure the absence of synergistic changes. Such strength of jelly corresponds to the high merchandising properties of the finished product.…”
Section: Research Resultsmentioning
confidence: 99%
“…From a literary source [16] it is known that ionotropic adhesion in a mixture of structure-forming agents with LPS, sodium alginate and calcium ions has a different flow rate and requires constant monitoring to obtain dredges with certain rheological properties. To achieve a controlled process, a pre-prepared mixture of the studied structure-forming agents is poured with a spicy broth [7] and heated. Heating prevents premature jelly formation by maintaining thermal movement of the polymer units and preventing the compound from reacting with calcium ions.…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve the objective, the following methods were used: -rheological with a PCE-RVI 2 V1L viscometer manufactured by PCE Instrument, Germany; -microscopic with a microscope LeicaDM4, Germany (250 x, 550x, 750x); -turbidimetric turbidity meter AMTAST AMT21, USA; -expert method based on the totality of all assessment points, taking into account the selected weighting factors [19].…”
Section: Methods Of Researchmentioning
confidence: 99%
“…When an emulsion is obtained in the technological system «oil -low-meth oxylated pectin -Ca 2+ », thermodynamic equilibrium is achieved, which corresponds to the development of the system when an ionic calcium solution is introduced into the technological medium of oil and pectin with the formation of a certain spatial structure. In oil-in-water emulsions of low methoxylation, pectin from apple pomace plays the role of an emulsifier and stabilizer [19].…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%